(untitled) (Research, Society and Development, 2019)
This study aims to analyze the perceptions of nursing students about the interconnections between the Nursing Process and the Systematization of Nursing Care. This is a descriptive, exploratory research with a qualitative approach, having as participants, twenty-five students of the discipline of Nursing in Adult and Elderly Health I of a university in Rio Grande do Sul, Brazil. Data collection took place in the second half of 2019, through the application of a semi-structured questionnaire. The analysis of the results followed the approximations with the Content Analysis of Bardin (2016). The results identified the participants’ knowledge and work methodologies. In this way, they understand that the Nursing Process consists of an integrated methodology of work that guides the realization of the care plan. Under the same threshold, it is identified that the Systematization of Nursing Care is articulated as a scientific support that fosters the qualification of patient care. Participants are considered to articulate the existing interconnections between both work methodologies, inferring about the precepts and benefits of their integrated realization.